Environmental Health Overview on Amaliun Street, Medan Area - Rani Suraya; Abid Farhan; Sakira Nabila Utami Siregar; Mely Febriani; Rabiatul Chazali; Iqbal Fathur Rifqy (KOLABORASI: Journal of Multidisciplinary, 2025)
This research aims to explore behavioral patterns and environmental conditions of households related to waste management, sanitation and cleanliness in a community. The research method was carried out using a questionnaire which was distributed directly to households, asking about activities such as waste disposal, sanitation of toddler feces, organic waste management, and disease prevention practices such as fighting mosquito bites. Apart from that, the questionnaire also evaluates the condition of the bedroom, kitchen, family room, and the main water source used. The research results show that although most households have systems for collecting waste water and adequate sanitation, there is still a tendency to dispose of waste directly into sewers or rivers. Even though the majority of households have a closed waste collection system, there are also those who still use open areas. Waste management is generally carried out by transporting it by officers or burning it, although there are still those who throw it in prohibited places. Prevention of diseases transmitted through mosquito bites is generally done by using anti-mosquito medication and regularly draining water reservoirs. Ventilation and lighting conditions in the house vary, but most are considered adequate. The majority of households rely on refillable water and drilled wells as the main water source, with an average water consumption of between 200 and 350 liters per day. This research provides a clear picture of household habits and environmental conditions, which is an important basis for developing sanitation and environmental improvement programs in the communities concerned.